2000
DOI: 10.1071/ch00011
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Protonation and Sodium Binding of Sulfate in Concentrated NaCl and CsCl Solutions Studied by Raman Spectroscopy

Abstract: The protonation constant (pKa) of SO42–(aq) has been determined at ionic strengths 0.5 M ≤I ≤4.0 M in NaCl and CsCl media at 25˚C by using Raman spectroscopy. These data were used to calculate the association constant of the NaSO4–(aq) ion pair in CsCl media. The results are in excellent agreement with previous values obtained by other techniques. The (pKa) was also measured at I = 4 M in both media at temperatures up to 85˚C and the associated enthalpy and entropy changes were calculated. However, reliable th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Recent simulation studies 29 have suggested that two types of hydration occur for the alkali metal cations, which the authors termed electrostatic (hydrophilic) ion solvation and cage formation (hydrophobic hydration). The former predominates with the smaller cations whereas the latter becomes important for the larger cations, resulting, for example, in a maximum in the solvation entropies as a function of ion size. , Circumstantial evidence for greater-than-expected binding of simple ligands by Cs + has also been obtained by Raman studies. , In particular, it was postulated that the extent of contact ion-pair (CIP) formation increased with increasing cation size as a result of the decreasing strength of the (primary) hydration sphere . This can occur even if the overall formation constant shows the opposite trend.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent simulation studies 29 have suggested that two types of hydration occur for the alkali metal cations, which the authors termed electrostatic (hydrophilic) ion solvation and cage formation (hydrophobic hydration). The former predominates with the smaller cations whereas the latter becomes important for the larger cations, resulting, for example, in a maximum in the solvation entropies as a function of ion size. , Circumstantial evidence for greater-than-expected binding of simple ligands by Cs + has also been obtained by Raman studies. , In particular, it was postulated that the extent of contact ion-pair (CIP) formation increased with increasing cation size as a result of the decreasing strength of the (primary) hydration sphere . This can occur even if the overall formation constant shows the opposite trend.…”
Section: Resultsmentioning
confidence: 99%
“…29,42 Circumstantial evidence for greater-than-expected binding of simple ligands by Cs + has also been obtained by Raman studies. 43,44 In particular, it was postulated that the extent of contact ion-pair (CIP) formation increased with increasing cation size as a result of the decreasing strength of the (primary) hydration sphere. 44 This can occur even if the overall formation constant shows the opposite trend.…”
Section: Possible Ion Pairing In Cscl(aq)mentioning
confidence: 99%
“…Elevated temperature Raman measurements were performed using a custom-made attachment (Ventacon, UK) as described elsewhere. 33 To check the reproducibility of the data, a few spectra were measured using a Bruker RFS-100 near IR FT-Raman spectrometer with Nd:YAG laser and Ge-diode detector as described elsewhere. 5, 6 The results were in quantitative agreement with those reported here.…”
Section: Methodsmentioning
confidence: 99%
“…Various authors studied [4][5][6][7][8][9][10], mainly by Raman spectroscopy, the distribution of HSO 4 − , SO 4 2− and of the molecular H 2 SO 4 in aqueous sulphuric acid solutions from 0 to 100 wt.% in acid, generally at 298.15 K. Spectra indicate that the molecular form appears only at acid concentrations larger than 20 M (M ≡ mol/L).…”
Section: Speciation Of Aqueous Sulphuric Acidmentioning
confidence: 99%